"Black Hole" Debt Restructuring and Banking Measures Strengthening Performance and Role of Intermediation: Islamic and Commercial Bank In Indonesian - Fasa, Muhammad Iqbal; Hendri, Loni; Suharto, Suharto (Integrated Journal of Business and Economics (IJBE), 2021)
This research aims to find credit restructuring "black hole," then draw some steps banks should do to strengthen its performance and its role as financial intermediary in COVID-19 condition. The descriptive-critical analysis is used in this paper. The analysis began by presenting data on credit restructuring, its forms used by national banks, and credit restructuring policy issued by OJK to anticipate negative impact of COVID-19 on banking activities. Analysis continued to application of the policy to find credit restructuring "black hole" on banks' performance and its intermediary financial role. Based on the analysis, some steps are recommended to followed by banks to strengthen its performance and intermediary financial role. This research found some credit restructuring "black hole." First, credit restructuring needs high capital and liquidity so that the banks which have low capital will be in trouble and will affect financial system nationally. Second, credit restructuring needs some sorting process, which will exclude unpotential debitur. Third, uncertainty of recovery process of debitur as impact of COVID-19. Forth, how long banks could use credit restructuring while maintaining its performance and intermediary financial role. Hence, credit restructuring would not be enough for banks to play its role in supporting debitur, maintain its business, strengthen its performance and intermediary financial role, and positively play role for economic growth and society. This research suggests five concrete steps banks could use to strengthen its performance and financial intermediary role.